2016
DOI: 10.1186/s13054-016-1207-7
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin administration is associated with a lower incidence of acute kidney injury after cardiac surgery: a propensity score matched study

Abstract: BackgroundSystemic inflammation is involved in the development of acute kidney injury (AKI) after cardiac surgery with cardiopulmonary bypass (CPB). Ulinastatin, a urinary trypsin inhibitor (UTI), possesses a variety of anti-inflammatory effects. Therefore, we hypothesized that the administration of ulinastatin would reduce the occurrence of AKI in patients undergoing cardiac surgery with CPB.MethodsA retrospective propensity score matched analysis was used to evaluate the effect of ulinastatin on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Compared with ulinastatin, aprotinin, a serine protease inhibitor derived from bovine lung tissue which has antifibrinolyticand anti-inflammatory effects (41), was mainly used to reduce perioperative bleeding and transfusion in cardiac surgery (42), but its renoprotectiverole is still controversial (43-45). In addition, the protective role of ulinastatin was also confirmed by a propensity score matched study (46). Further prospective, randomized, controlled trials are warranted to confirm the protective role of ulinastatin in the development of CSA-AKI.…”
Section: Discussionmentioning
confidence: 80%
“…Compared with ulinastatin, aprotinin, a serine protease inhibitor derived from bovine lung tissue which has antifibrinolyticand anti-inflammatory effects (41), was mainly used to reduce perioperative bleeding and transfusion in cardiac surgery (42), but its renoprotectiverole is still controversial (43-45). In addition, the protective role of ulinastatin was also confirmed by a propensity score matched study (46). Further prospective, randomized, controlled trials are warranted to confirm the protective role of ulinastatin in the development of CSA-AKI.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the release of inflammatory mediators serves an important role in the occurrence and development of COPD; in addition, protease/anti-protease imbalance serves an important role in the pathogenesis of COPD (23). Previous studies have revealed that ulinastatin, a type of broad-spectrum protease inhibitor, can reduce tissue damage by inhibiting the release of inflammatory mediators, as observed in acute kidney injury (24), acute pancreatitis (25) and acute lung injury (7,26); however, there are very limited reports on the treatment of COPD with ulinastatin. Therefore, in the present study COPD rat models were established, and underwent ulinastatin treatment, to determine whether ulinastatin had an effect on COPD; which may eventually lead to the elucidation of the underlying disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown that ulinastatin may reduce the risk of acute kidney injury after CPB, but this finding is controversial because of the absence of a difference in the s-Cr or cystatin C concentration after aortic valve surgery with CPB. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%